2010
DOI: 10.1016/j.jpor.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of denture cleansers on physical properties of heat-polymerized acrylic resin

Abstract: Although the color changes after the immersion in denture cleansers were clinically insignificant, the Corega Tabs group showed higher color differences. The Bony Plus group showed significantly increased surface roughness. Both effervescent tablets Corega Tabs and Bony Plus significantly diminished the flexural strength of the acrylic resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
152
7
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(199 citation statements)
references
References 32 publications
15
152
7
16
Order By: Relevance
“…The result of this study is consistent from those of Ünlü et al 19) and Peracini et al 1) , who also detected a significant whitening effect on heat polymerized acrylic resins with perborate cleansing agents. However, Sato et al 30) did not detect color changes in the PMMA based acrylic resins with the use of three different denture cleansers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The result of this study is consistent from those of Ünlü et al 19) and Peracini et al 1) , who also detected a significant whitening effect on heat polymerized acrylic resins with perborate cleansing agents. However, Sato et al 30) did not detect color changes in the PMMA based acrylic resins with the use of three different denture cleansers.…”
Section: Discussionsupporting
confidence: 92%
“…Peracini et al 1) immersed acrylic resin samples in alkaline peroxide solution for 6 days and reported that surface roughness of the resins were increased. This finding is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been reports of titanium alloy tarnishing (surface discoloration) 12 and corrosion (surface pitting). 13 Previous studies have evaluated color alterations in acrylic resins treated with 0.5% and 1% hypochlorite alkaline solutions, 7,14,15,16 as well as with alkaline peroxide solutions, 7,17,18 and they have revealed that the type of sanitizer, the immersion time, and the period of use are factors to be considered. In relation to the metal surface, it was determined that tarnish and spot corrosion on Co-Cr alloys are deleterious effects of immersion in cleansing solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Peracini ve ark. 13 , alkalin peroksit içerikli temizleyici solüsyonların akrilik rezinlerin yüzey pürüzlülüğünü anlamlı olarak arttırdığını rapor etmiĢtir. Panariello ve ark.…”
unclassified